Keragaan Bibit Bud Chips Tebu (Saccharum officinarum L.) dengan Perlakuan Lama Perendaman dan Konsentrasi IAA - Irda Nila Selvia; Meiriani Meiriani; Yaya Hasanah (Jurnal Agroekoteknologi, 2015)
The objectives of the research was to study performance of sugarcane bud chips with soaking timeand IAA concentration treatment. The research was carried out at PT. Perkebunan Nusantara IITanjung Jati, Langkat (± 40 m slr) on May – August 2014. The research used factorial RandomizedBlock Design (RBD) with two factors and three replications. The first factor was soaking time with3 levels (10; 20; and 30 minutes) and the second factor was IAA concentration with 4 levels (0;100; 200; and 300 ppm). Data were analized with Analysis of Variance and continued withDuncan’s Multiple Range Test (DMRT). The variables observed were plant height, number ofleaves, and total leaf area. The result of research showed that the best performance of sugarcane budchips was at 20 minutes of soaking time and 200 ppm of IAA concentration that was showed by theheighest plant height 10 week after transplanting (WAT), in great quantities number of leaves 10WAT and the widest total leaf area 10 WAT was 20 minutes of soaking time and 200 ppm of IAAconcentration.Key words: sugarcane, bud chips, soaking time, IAA concentration